COVERING PHYSICAL EDUCATION ISSUES IN THE FIRST STEP CURRICULUM - Muxitdinova Nigora Mexriddinovna (International Engineering Journal For Research & Development, 2022)
The article describes the features, goals and objectives of physical education under the "First Step" program